Use of Viber Platform as a Social Media Application in TEFLat Erbil Polytechnic University - Hasan Azeez, Nadhim; Mohammed Mustafa, Awat (International Journal of Psychosocial Rehabilitation, 2019)
The use of social media platforms has become very popular in recent years. Academic institutions such as universities, colleges and institutes around the world have adopted such platforms into their educational systems for educational purposes. One of the popular and practical platforms providing such opportunities is Viber. This paper examines the usefulness of Viber as a social media platform for English language learners at the language centre of Erbil Polytechnic University (EPU). The study is conducted on 40 participants (24 males and 16 females)of two IELTS preparation courses with a pre-intermediate language proficiency level who wanted to take the IELTS test as part of the requirements for obtaining academic titles or joining postgraduate studies in Kurdistan Region Universities. The researchers adopted a quantitative approach to collect data from the participants. An original questionnaire was designed through the free online Google form that consisted of 18 Wh and Yes/No questions. The learners’ thoughts about the usefulness of the platform were investigated in regards to motivation, L2 promotion and learning targets. Online access to the questionnaire was provided at the end of the preparation courses in order to give the learners a chance to express their perceptions on the progress of language learning. The results of the study show that the majority of the learners (32 learners out of 40)think that such platforms are effective and necessary in English language teaching (ELT) courses for encouraging learners to practice the target language and motivate them to be independent learners. A large population of this study were above the age of 30 years old, therefore, the most significant finding of this research is that not only the new generation of learners, but also senior learners (people over 30 years of age) are also interested in the use of social media in TEFL courses. This could provide help for English language teachers to implement the use of social media networks into their language classes.